Mashing with unmalted sorghum using a novel low temperature enzyme system: impacts of sorghum grain composition and microstructure - Holmes, Calum P.; Casey, John; Cook, David (Elsevier, 2017)
Brewing lager beers from unmalted sorghum traditionally requires the use of high temperature mashing and exogenous enzymes to ensure adequate starch conversion. Here, a novel low-temperature mashing system is compared to a more traditional mash in terms of the wort quality produced (laboratory scale) from five unmalted sorghums (2 brewing and 3 non-brewing varieties). The low temperature mash generated worts of comparable quality to those resulting from a traditional energy intensive mash protocol. Furthermore, its performance was less dependent on sorghum raw material quality, such that it may facilitate the use of what were previously considered non-brewing varieties. Whilst brewing sorghums were of lower protein content, protein per se did not correlate with mashing performance. Rather, it was the way in which protein was structured (particularly the strength of protein starch interactions) which most influenced brewing performance. RVA profile was the easiest way of identifying this characteristic as potentially problematic.